Recycling Efficiency and Waste Minimization through Students’ Behaviour on the University of Leicester Campus - Abdulkhaliq Abdullah, Rebeen; Majed Sadq, Zana; Othman, Bestoon; Tareq Faeq, Dastan (International Journal of Psychosocial Rehabilitation, 2019)
Waste is generated from all materials placed on the market in different ways. The volumes of municipal waste in general and in the institutions of higher education in particular, one of which is a case study in this research, have been rising over the years almost everywhere in the world. This research is an investigation of recycling efficiency and waste minimisation through students’ behaviour on the University of Leicester campus, conducted by a questionnaire and an interview survey. The purposes of the study are: first, to examine the students’ environmental awareness and determine its impact on the waste management system; second, to demonstrate the impacts of students’ attitudes and behaviors towards recycling and waste minimising on campus; and finally, to identify factors that affect students’ recycling and waste minimising habits, such as demographic, external, and internal factors. The results show that the level of students’ environmental awareness is low due to lack of knowledge about environmental sustainability. Another finding was that students are willing to carry out recycling and pro-environmental behaviour; nevertheless, more facilities and more efforts are needed for students to gain a better understanding of environmental sustainability and waste management. Moreover, the main barriers preventing students from recycling are lack of information about environmental protection and lack of facilities on the campus.